PENGARUH MODEL PEMBELAJARAN THINGKING ALOUD PAIR PROBLEM SOLVING (TAPPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP N 13 MERANGIN - Ida Khotimah; Yohanes; Hidayati Rais (Hira Institute, 2025)
Students' limited numerical problem-solving capacities propelled this investigation. This will be determined based on the classical score set by the school, specifically 70%. To attain this classical score, 22 students must reach the KKM, indicating that their capacities are considered good. Be that as it may, within the restatement of the scientific issue regarding capacity test scores, it was found that only 12 students met the KKM. Separated from that, if you look at the understudy learning exercises, students are less dynamic with a rate of 31.18% during the learning process. Another thing is that the learning utilized still employs ordinary learning. This will be seen from the findings of interviews conducted by analysts with instructors and perceptions of instructor exercises during learning. This research aims to describe mathematical problem-solving abilities using the Thinking Aloud Pair Problem Solving learning, which is superior to routine learning for lesson VIII students. The strategy utilized in this study is a test-based research strategy. To test the speculation, the t-test is utilized. The esteem of t_(calculated )=2.65 and the esteem of t_(table )=1.67. In agreement with the choice making criteria for the right-hand test, in case t_(count )>t_(table) or 2.65>1.67, at that point H_(0) is rejected and H_(1) is acknowledged, meaning that scientific problem solving capacities are instructed utilizing the demonstrate Considering Out loud Combine Issue Understanding learning is superior than conventional learning for lesson VIII understudies at SMP N 13 Merangin for the 2024/2025 scholarly year.